ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS XI MELALUI PENDEKATAN METAKOGNITIF - Ajeng Yulia Rahmawati; Euis Eti Rohaeti; Anik Yuliani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research is a quantitative research that aims to (1) examine the differences of students 'mathematical critical thinking ability in terms of  self regulated learning which gain learning with metacognitive approach and students who only get ordinary learning (2) examine the influence of self regulated learning on students' mathematical critical thinking ability and (3) to describe students' mathematical critical thinking skills in terms of self regulated learning. Subjects in this research were students of class XI in MAN 1 Cimahi with the subject amounted to 64 students consisting of the control class and experimental class. Subjects were divided into three groups based on self-regulated learning level,  specifically high level, medium level, and low level. Based on the results of the research, it’s found that (1) the ability of mathematical critical thinking in the experimental class is better than the mathematical critical thinking ability of the control class (2) the students' self-regulated learning of the experimental group positively influences the critical thinking skills of mathematics (3) The students of high level already able the indicators of critical thinking ability. The students of medium level are still experiencing errors in the algorithm resulting in incorrect results and conclusions. The Students of low level have not been able to meet the indicators of critical mathematical thinking ability.